Pengaruh Return On Asset (ROA), Return On Equity (ROE), dan Earning Per Share (EPS) Terhadap Harga Saham di Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Bekti Mayasari; Endang Sri Utami (Jurnal Riset dan Inovasi Manajemen, 2023)
This research was conducted with the aim of knowing the effect of return on assets, return on equity and earnings per share on stock prices in banking companies listed on the IDX for the 2019-2021 period. The sample used in this research is 10 companies. Sampling was done by purposive sampling method. The method used is a quantitative approach. Data analysis techniques used include: classical assumption test, multiple linear regression test, hypothesis test and coefficient of determination test. The results showed that the return on assets and return on equity variables partially did not have a significant effect on stock prices, while earnings per share had a significant effect on stock prices. The results of the study simultaneously (return on assets, return on equity and earnings per share) have a significant effect on stock prices.